Intestinal epithelial exosomes carry MHC class II/peptides able to inform the immune system in mice. Issue 12 (21st November 2003) - Van Niel, G; Mallegol, J; Bevilacqua, C; Candalh, C; Brugière, S; Tomaskovic-Crook, E; Heath, J K; Cerf-Bensussan, N; Heyman, M
Abstract : Background: Intestinal epithelial cells secrete exosome-like vesicles. The aim of this study was to characterise murine intestinal epithelial exosomes and to analyse their capacity to inform the immune system in vivo in mice. Methods: Epithelial exosomes were obtained from the murine epithelial cell line MODE K incubated in the presence or absence of interferon γ (IFN-γ) together with pepsin/trypsin ovalbumin hydrolysate (hOVA) to mimic luminal digestion. Exosomes isolated from MODE K conditioned media (EXO-hOVA and EXO-hOVA-IFN) were characterised by western blot, peptide mapping, and mass spectrometry. They were injected intraperitoneally to C3H/HeN mice to test their immunocompetence. Results: MODE K epithelial exosomes displayed major histocompatibility complex (MHC) class I and class II (upregulated by IFN-γ) molecules and tetraspan proteins (CD9, CD81, CD82) potentially involved in the binding to target cells. A33 antigen, an Ig-like molecule highly specific for intestinal epithelial cells, was enriched in exosomes and was also found in mice mesenteric lymph nodes, suggesting exosome migration towards the gut associated lymphoid tissues. Intraperitoneal injection of EXO-hOVA or EXO-hOVA-IFN did not induce humoral or cellular tolerance to OVA in mice. In contrast, exosomes obtained after incubation with IFN-γ (EXO-hOVA-IFN), bearing abundant MHC class II/OVA complexes, induced a specific humoral immune response. Conclusions: Epithelial exosomes are antigen presenting vesicles bearing MHC class II/peptide complexes that prime for an immunogenic rather than tolerogenic response in the context of a systemic challenge. In the intestine, both the mucosal microenvironment and local effector cells are probably key players in determining the outcome of the immune response to exosome derived epitopes.